Economic, Social, and Environmental Impacts of the Economic Empowerment Program in Gampong Kuta Barat, Sukakarya District, Sabang City, Aceh Province - Teguh Try Hartono (Prospect Publishing, 2023)
Sabang City, Aceh Province has marine capture fisheries production reaching 5,150 tons in 2015 (BPS Aceh, 2015). The fishing profession is one of the professions of the majority of the population. Despite having abundant catches, fishermen in this village still carry out simple fish production. The caught fish is sold and if it does not sell well it is smoked for resale. This fish processing process has not optimally provided economic value to the community and provided excess carbon emissions. Seeing this potential and problem, PT Pertamina (Persero) MOR I Fuel Terminal Sabang conducts an economic empowerment program for fish management in the form of providing capital and business facilities, providing business development assistance, entrepreneurial training, and business assistance. The program is evaluated to determine economic, social, and environmental impacts with a descriptive qualitative research approach. The result of this research is that the fish processing economic empowerment program carried out by PT Pertamina (Persero) MOR I Fuel Terminal Sabang has a significant impact on the economic, social, and environmental sectors. The economic impact can be seen from the economic addition of fishermen of the Pepper Garden Group (Kkemer) of Rp8,000,0000 per month from fish processing in the form of raw and fried crackers, fish chips, nuggets, and other processed fish products. Socially, the impact of this empowerment program is the creation of a system of work/management of fish products which was originally carried out individually into groups, has group independence that can carry out production functions consistently and active involvement of stakeholders. While the positive environmental impact is shown by reducing carbon emissions in the air by 105 Kg CO2 per month resulting from changing fish processing by tapping into drying and frying.